AKTA BORGTOCHT DALAM PERJANJIAN KREDIT - William, G Victor (JURNAL MEDIA HUKUM DAN PERADILAN, 2019)
Personal guarantee (borgtocht) is an additional agreement (accesoir) which is made for the benefit of the creditor. Personal guarantee cannot exist if there is no legal principal agreement between the creditor and the debtor, therefore this guarantee agreement involves three parties, namely the creditor, the debtor and the guarantor. The main reason for the making of personal guarantee agreement is because there is a relationship of interest between the guarantor and the debtor (the guarantor has an economic interest in the business of the debtor). Personal guarantee in practice are always made in written form. Personal guarantee agreement can be made in the form of under the hand deed or notarial deed. In banking practices, the agreement is made in the form of a standard contract that has been provided by the bank as the creditor. The party that signs this deed is the debtor and the guarantor, hereinafter the deed kept by the bank.